QUIC Delay Control: an Implementation of Congestion and Delay Control - Saverio Mascolo; Andrea Balillo; Gioacchino Manfredi; Davide D’Agostino; Luca De Cicco (2025 17th International Congress on Ultra Modern Telecommunications and Control Systems and Workshops (ICUMT), 2025)
A new congestion and delay control algorithm named QUIC-Delay Control (QUIC-DC) is proposed for controlling not only congestion but also the queueing delay encountered along the forward communication path. The core idea is to estimate the one-way queueing delay of a connection to trigger an early reaction to congestion. This idea, along with the TCP Westwood+ congestion control algorithm, has been implemented in QUIC-DC and compared with QUIC Cubic, BBRv2, NewReno, Westwood+. The results obtained in the emulated and real network environments show that QUIC-DC can significantly reduce packet losses along with end-to-end communication delays, while preserving network utilization, features that are both very useful for real-time applications.
Keywords: Conferences; Packet loss; Control systems; Real-time systems; Delays; Telecommunications; Internet; Distribution functions; Congestion Control; Delay Control; QUIC